UNDERSTANDING FACTORS INFLUENCING THE ADOPTION OF QRIS AMONG YOUNG ADULTS IN BANDUNG: AN EXTENDED UTAUT2 APPROACH WITH PERCEIVED RISK AND TRUST - Ratufariza, Sazki
Amidst the acceleration of widespread digital transformation, payment technology has undergone an evolution, marking a paradigm shift from cash to digital transactions. In this context, Quick Response Code Indonesia Standard (QRIS) is emerging as a promising payment solution, integrating technology with daily activities to expand financial access. This study aims to identify and analyze the factors that influence the acceptance and use of QRIS among young adults in Bandung. Using the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model, which is extended with Perceived Risk and Trust dimensions, this study examines how these variables affect Behavioral Intention (BI) and Actual Use (AU) of QRIS. Trust is important in QRIS acceptance as it affects users' perceived security and convenience in digital transactions, motivating users to adopt and continue using QRIS. Meanwhile, Perceived Risk includes concerns about data security and potential financial loss, which are important considerations in managing user trust. Through an online survey, data was collected from 227 respondents who are young adults in Bandung, using Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique for data analysis. The results showed that Trust has a significant and positive influence on behavioral intention and actual use of QRIS. Meanwhile, Perceived Risk did not show any significant influence. In addition, factors such as Effort Expectancy, Facilitating Conditions, Hedonic Motivation, and Habit positively influence QRIS BI and AU. Furthermore, BI positively influences AU. This study confirms the importance of developing strategies aimed at increasing user trust in QRIS payment systems to encourage wider and more effective adoption among the public. However, this study is limited to young adults of Bandung City, which may underestimate the findings. Future research should explore Trust and Perceived risk to moderate other factors, use different methodological approaches for deeper understanding, and consider a wider sample.